Relationship between physico-chemical characteristics and potential toxicity of PM10. (November 2016) - Megido, Laura; Suárez-Peña, Beatriz; Negral, Luis; Castrillón, Leonor; Suárez, Susana; Fernández-Nava, Yolanda; Marañón, Elena
Abstract: PM10 was sampled at a suburban location affected by traffic and industry in the north of Spain. The samples were analysed to determine the chemical components of PM10 (organic and elemental carbon, soluble chemical species and metals). The aim of this study was to assess the toxicity of PM10 in terms of the bulk analysis and the physico-chemical properties of the particles. Total carbon, sulphates, ammonium, chlorides and nitrates were found to be the major constituents of PM10. The contribution of the last of these was found to increase significantly with PM10 concentration (Pearson coefficient correlation of 0.7, p-value < 0.001). Individual airborne particles were characterised morphologically and chemically via a combination of Scanning Electron Microscopy and Energy-Dispersive X-ray spectroscopy (SEM-EDX). The subsequent image analysis revealed C-rich particles with shapes that pointed to combustion processes. Moreover, carbonaceous particles seemed to act as vehicles for sulphur compounds and metals (S, Na, Fe, Ca, Mg, K, Al, Mn, Zn and Cu). Coarse particles were found to be mainly constituted by crustal material and marine and carbonaceous particles. Although most of the studied individual particles in PM10 samples (86.0%) had a diameter within the 0.1–2.5 μm range, 1.8% of them had sizes lower than 0.1 μm 40.2% of the total studied particles were estimated to be inhaled and deposited in the human respiratory tract; 12.3% of these particles would reach the deepest zones, thereby posing a major risk to human health. Highlights: Toxicity of PM10 was assessed based on physico-chemical characterisation. Crustal, marine and carbonaceous particles were predominant in the coarse fraction. Carbonaceous particles served as vehicles for metals and sulphur compounds. PM10 levels and nitrate concentrations presented a positive linear relationship. Over 40% of the PM10 particles would be deposited in the human respiratory tract.